Deelnemende en verteenwoordigende burgerskap; Die ontwikkeling van politieke medeseggenskap in die Nederlandse Protestantse denke - Raath, Andries (Tydskrif vir Christelike Wetenskap | Journal for Christian Scholarship, 2024)
Dutch constitutional thought of the sixteenth century contributed in major respects to Protestant views on liberty, participatory and representative government and resistance to tyranny. Martin van Gelderen describes the essence and defining characteristic of Renaissance republicanism and adds that, as supreme political values, liberty, the common good of the community and the personal freedom of its members were preserved and furthered best by a political system characterized by a set of sound laws, a refined form of mixed government based on elections (and thus on representation) and virtuous acts of public service by the citizens, and also that it is worthwhile to compare the ideology developed during the Dutch Revolt, which contained a vision of the political order as based on liberty, constitutional charters, representative institutions and popular sovereignty. This article investigates the contribution of three texts in particular to the notions of participatory and representative governance in the protection of civil liberties in sixteenth century political discourse viz. A defence and true declaration (1571), Political education (1582) and the Short exposition (1582). It is concluded that the values of participatory and representative political bodies, are, together with other core-values, an equally important legacy of Marnix van St. Aldegonde and other authors to the development of a strong democratic and constitutionally based theory of people’s resistance to tyranny.